Limitation of Colibactin from Klebsiella Pneumonia - Mahmood, Walaa Shakir (Journal of Science in Medicine and Life, 2024)
Klebsiella pneumoniae is the primary pathogen responsible for most cases of meningitis in the community. Nevertheless, the absence of a biologically significant meningitis model for K. pneumoniae has hindered investigations into its pathogenesis mechanism. The highly virulent K1 K. pneumoniae strains, linked to adult meningitis, are predominantly part of a unified clonal complex. Certain strains of K. pneumoniae contain a genetic cluster that is in charge of producing colibactin. Colibactin is a compact molecule with genotoxic properties that is produced through biosynthesis and is governed by genes found on the gene island. In contrast to other highly infectious K. pneumoniae that mainly target the liver, the K1 strains that produce colibactin showed a strong preference for infecting the brain. A meningitis model that is relevant to physiology using K1 K. pneumoniae. Successful induction of acute meningitis was achieved by inoculating K1 K. pneumoniae via orogastric, intranasal, and intravenous routes. In addition to the usual signs of bacterial meningitis, the colibactin-producing K1 K. pneumoniae strain also caused severe DNA damage and individual cell death. Removing the gene that stops the production of colibactin significantly reduced the ability of K. pneumoniae to cause severe illness in the crucial stages of meningitis formation. Colibactin is required, but not the only factor, for the ability of K1 K. pneumoniae to infect the meninges. The bacterial genotoxin colibactin disrupts the eukaryotic cell cycle by inducing double-stranded DNA breaks. It has been associated with bacterially triggered colorectal cancer in individuals. Enterobacteriaceae encodes Colibactin in a 54kb genomic region.